Professionalism and Staff Development in Managing Business Education Programme in South-South Nigerian Public Universities: A Comparative Relationship - Liadi, Hakeem Olaniyi; Samsom, Agatha (NIU Journal of Educational Research, 2025)
This study investigated the relationship between professionalism and staff development in the efficient management of business education programmes at Nigerian universities in the South-South area. To do this, three research questions were addressed and three hypotheses were tested at a significance level of 0.05. A descriptive survey approach was used, with a population of 98 business instructors from five selected universities in the South-South geopolitical zone. Given the population's manageable size, the sample includes all 98 business educators. Data was collected using an instrument titled “Professionalism and Staff Development on Effective Management of Business Education Program Questionnaire” (PSTDEMBEPQ), which was validated by a business education expert. The correlation coefficient of the instrument was determined to be 0.736. The findings revealed a moderate overall level of professionalism among educators, although there were variations across the different assessed areas. These variations highlight the need for ethical training, effective workload management strategies, and professional development programmes to enhance the professionalism of business educators in the region. Furthermore, the results indicated a moderately positive and statistically significant relationship between staff professionalism and the effective management of business education programmes. The study concludes that professionalism and staff development are critical for the effective management of business education programmes in South-South Nigerian universities. It identifies an overall moderate level of professionalism, suggesting opportunities for improvement and emphasizing the necessity for targeted interventions. The study recommends that universities prioritize ongoing professional development by allocating funds and facilitating access to workshops, conferences, certifications, and online courses. Keywords: Professionalism, Staff Development, Effective Management, Business Education programme, South-South Universities